5-year follow-up of the randomised Diabetes Remission Clinical Trial (DiRECT) of continued support for weight loss maintenance in the UK: an extension study - Lean, Michael Ernest John; Leslie, Wilma S; Barnes, Alison C; Brosnahan, Naomi; Thom, George; McCombie, Louise; Kelly, Tara; Irvine, Keaton; Peters, Carl; Zhyzhneuskaya, Sviatlana; Hollingsworth, Kieren G; Adamson, Ashley J; et al. (The lancet. Diabetes & Endocrinology, 2024)
Background - In DiRECT, a randomised controlled effectiveness trial, weight management intervention after 2 years resulted in mean weight loss of 7·6 kg, with 36% of participants in remission of type 2 diabetes. Of 36 in the intervention group who maintained over 10 kg weight loss at 2 years, 29 (81%) were in remission. Continued low-intensity dietary support was then offered up to 5 years from baseline to intervention participants, aiming to maintain weight loss and gain clinical benefits. This extension study was designed to provide observed outcomes at 5 years. - Methods - The DiRECT trial took place in primary care practices in the UK. Participants were individuals aged 20-65 years who had less than 6 years’ duration of type 2 diabetes, a BMI greater than 27 kg/m2, and were not on insulin. The intervention consisted of withdrawal of antidiabetic and antihypertensive drugs, total diet replacement (825-853 kcal per day formula diet for 12-20 weeks), stepped food reintroduction (2-8 weeks), and then structured support for weight-loss maintenance. After sharing the 2-year results with all participants, UK National Health Service data were collected annually until year 5 from remaining intervention participants who received low-intensity dietary support, intervention withdrawals, and the original randomly allocated groups. The primary outcome was remission of type 2 diabetes; having established in the DiRECT trial that sustained weight loss was the dominant driver of remission, this was assumed for the Extension study. The trial is registered with the ISRCTN registry, number 03267836. - Findings - Between July 25, 2014, and Aug 5, 2016, 149 participants were randomly assigned to the intervention group and 149 were assigned to the control group in the original DiRECT study. After 2 years, all intervention participants still in the trial (101 [68%] of 149) were approached to receive low-intensity support for a further 3 years. 95 (94%) of 101 were able to continue and consented and were allocated to the DiRECT extension group. 54 participants were allocated to the non-extension group, where intervention was withdrawn. At 5 years, DiRECT extension participants (n=85) lost an average of 6·1 kg, with 11 (13%) of 85 in remission. Compared with the non-extension group, DiRECT extension participants had more visits with HbA1c <48 mmol/mol (<6·5%; 36% vs 17%, p=0·0004), without glucose-lowering medication (62% vs 30%, p<0·0001), and in remission (34% vs 12%, p<0·0001). Original control participants (n=149) had mean weight loss 4·6 kg (n=82), and 5 (5%) of 93 were in remission. Compared with control participants, original intervention participants had more visits with weight more than 5% below baseline (61% vs 29%, p<0·0001), HbA1c below 48 mmol/mol (29% vs 15%, p=0·0002), without antidiabetic medication (51% vs 16%, p<0·0001), and in remission (27% vs 4%, p<0·0001). Of those in remission at year 2, 26% remained in remission at 5 years. Serious adverse events in the original intervention group (4·8 events per 100 patient-years) were under half those in the control group (10·2 per 100 patient-years, p=0·0080). - Interpretation - The extended DiRECT intervention was associated with greater aggregated and absolute weight loss, and suggested improved health status over 5 years. - Funding - Diabetes UK.
Online verfügbar: 26. Februar 2024, Artikelversion: 19. März 2024
Gesehen am 28.01.2025